1984
DOI: 10.1111/j.2042-3306.1984.tb01966.x
|View full text |Cite
|
Sign up to set email alerts
|

Contagious equine metritis — Use of gas liquid chromatography in identifying the causal agent

Abstract: Summary Cellular fatty acid compositions of contagious equine metritis isolates and three reference Haemophilus equigenitalis cultures were determined by gas chromatography. The chromatographic data were standardised and normalised fatty acid methyl ester (FAME) profiles were produced. The profiles were compared visually and similarity indices were determined using a computer peak matching method. There was little difference between the profiles of the three reference strains, each strain being characterised b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…18 : 0), the profiles of T. equigenitalis and the donkey isolates were similar. The characteristics shown are in agreement with those reported for T. equigenitalis (Neill et al, 1984 ;Sugimoto et al, 1982 ;Vandamme et al, 1998).…”
Section: Cellular Fatty Acid Analysissupporting
confidence: 91%
“…18 : 0), the profiles of T. equigenitalis and the donkey isolates were similar. The characteristics shown are in agreement with those reported for T. equigenitalis (Neill et al, 1984 ;Sugimoto et al, 1982 ;Vandamme et al, 1998).…”
Section: Cellular Fatty Acid Analysissupporting
confidence: 91%
“…After 1 h, 400 ,ul of buffer was removed and 20 U of restriction endonuclease (GIBCO/BRL or New England BioLabs, Inc.) was added. Restriction digestion was performed for 6 to 12 h. 8.3]-44.5 mM boric acid-1.25 mM disodium EDTA) at 90 V. The FIGE program consisted of 6 to 12 identical cycles of 4 h. An exponentially increasing forward switch time (0.05 to 55 s) was used; 50% of the switch time was reached at 40% of the cycle time. The reverse time phase and the pause time were 33 and 2%, respectively, of the forward time phase.…”
Section: Methodsmentioning
confidence: 99%
“…Cellular fatty acid composition of T. equigenitalis was determined by gas chromatography. Fatty acid methyl ester (FAME) profiles have shown that T. equigenitalis contains 3 major fatty acids including C 18: 1, C 16:0, and 30H-C 14:0 (22).…”
Section: Introductionmentioning
confidence: 99%